Ninkô no junan - Niwatsukino, Norihiro, 1981-; Tsujioka, Masato, 1979-; Wakabayashi, Miho; Iwahashi, Hideta; IndiePix (Firm); Tricycle Film (Firm); Soundview Media Partners ([New York, N.Y.] : Tricycle Film, 2016)
Ninko, a diligent young Buddhist monk, has a serious problem: women, and some men, find him sexually irresistible. After a troubling encounter with a naked masked woman, he sets out on a journey to purify himself of these sexual advances and haunting fantasies. Blends live-action and Japanese woodblock printing (Ukiyo-e) and animated sequences.
Originally released as a motion picture in 2016.
Masato Tsujioka, Miho Wakabayashi, Hideta Iwahashi, Yukino Arimoto.
Cinematographers, Takayuki Okazaki, Shunichiro Yamamoto ; editor, Norihiro Niwatsukino ; music, Office Higuchi.
In Japanese with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 12, 2019)
Keywords: Buddhist monks -- Drama; Murder -- Drama; Sex customs -- Drama; Feature films; Fiction films; Internet videos; Streaming video